Interferometric radar observations of filamented structures due to plasma instabilities and their relation to dynamic auroral rays. - Grydeland, Tom; Hagfors, T.; Trondsen, T.S.; Blixt, Erik Mårten; Løvhaug, Unni Pia; La Hoz, Cesar (European Geosciences Union, 2004)
Several explanations have been proposed for Naturally Enhanced ion-acoustic Echoes observed at midand high-latitude Incoherent Scatter observatories. A decisive measure for distinguishing between these explanations is whether or not simultaneously observed up- and downshifted enhancement occur simultaneously, or if they are the result of temporal and/or spatial averaging. The EISCAT Svalbard Radar has two antennas in the same radar system, which can be used as an interferometer when pointed parallel. In observations from 17 January 2002, between 06:46:10 and 06:46:30 UT, we used this possibility, in combination with direct sampling of the received signals, to yield measurements of “naturally enhanced ion-acoustic echoes” with sufficiently high resolution to resolve such averaging, if any. For the first time, radar interferometry has been employed to estimate the sizes of coherent structures. The observations were coordinated with an image intensified video camera with a narrow field of view. Together, this forms the initial study on the causal relationships between enhanced echoes and fine structure in the auroral activity on sub-kilometer, sub-second scales. The results confirm that the enhanced echoes originate from very localised regions ( 300m perpendicular to the magnetic field at 500 km altitude) with varying range distribution, and with high time variability ( 200 ms). The corresponding increase in scattering cross section, up to 50 dB above incoherent scattering, eliminates theoretical explanations based on marginal stability. The simultaneously observed up- and down-shifted enhanced shoulders, when caused by sufficiently narrow structures to be detected by the interferometer technique, originate predominantly from the same volume. These results have significant impact on theories attempting to explain the enhancements, in particular it is found that the ion-electron two-stream mechanism favoured by many authors is an unlikely candidate to explain the observations. The video data has helped establish a ...